Farmers’ Perception towards Organic Fertilizers in Kutch District of Gujarat, India - Tejas T. Chauhan; Chetan R. Dudhagara; Ashish B. Mahera (Archives of Current Research International, 2024)
Agriculture is backbone of the Indian economy. In India, about 60 to 70 per cent of the population is employed in agriculture, which generates around 20 per cent of the GDP of the nation. There is a shift observed in fertilizer usage. Different agencies are laying emphasis on the use of organic fertilizer. The study on farmers’ perception towards organic fertilizers in Kutch district of Gujarat was carried out. Multi stage sampling was used to select 200 respondents from the Anjar, Bhachau, Bhuj, Mandvi & Nakhtrana talukas of Kutch district. The result indicates that majority of farmers were male and they are in the 36 to 50 years age group, about half of the respondents were having family size of 3 to 5 members. About the respondents, 37% of the farmers had primary education, 24% had secondary education, and 17% were illiterate. The main source of income of the farmers was agriculture and the income of majority farmer is between 1 lakh to 2.5 lakh. Average land holding size of farmers was less than 5 acres. Irrigated farming was practiced by most of the farmers and tube well found to be the main source of irrigation. Main crop was Pomegranate with 51.00 per cent followed by Castor, Cotton, Vegetable crops and other crops. All the farmers were aware about organic fertilizer and all were using organic fertilizer in their field. Most of the respondents strongly believed that application of organic fertilizer helps in improvement of the microbial activity and water retention capacity of soil. It was found that 163 farmers were using packaged organic fertilizers and all 200 farmers were using gaushala compost/farm yard manure, etc.